Effect of Ultrasound‐Guided Intercostal Nerve Block Versus Fluoroscopy‐Guided Epidural Nerve Block in Patients With Thoracic Herpes Zoster: A Comparative Study. (23rd September 2018) - Lee, Hyo Jeong; Park, Hong Souk; Moon, Hyun Im; Yoon, Seo Yeon
Abstract : Objectives: To compare the efficacy of a conventional fluoroscopy‐guided epidural nerve block and an ultrasound (US)‐guided intercostal nerve block in patients with thoracic herpes zoster (HZ). Methods: This work was a comparative study of 38 patients with thoracic HZ pain and a chest wall herpetic eruption, aged 18 years or older, with pain intensity of 5 or greater on a numeric rating scale (NRS) for less than a 1‐month duration. Patients were consecutively enrolled and assigned to 2 groups in which the intervention was either the US‐guided intercostal nerve block or the fluoroscopy‐guided epidural nerve block approach with the addition of a 5‐mL mix of 2.5 mg of dexamethasone plus 0.5% lidocaine. The primary outcome measure was the NRS score reduction for the pain. Secondary outcomes included the duration of treatment, number of repeated injections until the final visit, and proportion of patients with pain relief after the first and final visits. Results: All patients within both intervention groups showed significant pain relief on the NRS at the final follow‐up point ( P  < .05). There was no significant difference in the mean value of NRS improvement based on the intervention type. There was also no statistically significant difference in the duration of treatment and the frequency of injection for pain relief. Conclusions: These findings showed that both the US‐guided intercostal nerve block and the fluoroscopy‐guided epidural nerve block were effective in patients with thoracic HZ. Compared data showed no significant differences in the pain reduction, duration of treatment, and frequency of injection. The US‐guided intercostal nerve block, which is more accessible than the fluoroscopy‐guided epidural nerve block, might be an alternative option for thoracic HZ.